Nivel sérico de estradiol a la monta y su efecto sobre la tasa de concepción en alpacas - Díaz C., Arturo; Huamán U., Héctor; Camacho S., José; Ampuero B., Antonio; Quispe M., Daniel (Universidad Nacional Mayor de San Marcos, 2022)
6 páginas